AN ANALYSIS OF STUDENTS’ VOCABULARY MASTERY AT SMK GRAFIKA BINA MEDIA ANALISIS PENGUASAAN KOSAKATA SISWA SMK GRAFIKA BINA MEDIA - Laurensia, Feren; Nabila, Resti; Sitorus, Elsa Oktavia (Lembaga Penelitian dan Pendidikan Mandala, 2021)
In learning foreign language, one of the important aspects is vocabulary mastery. To converse perfectly in one foreign language, one should have the sufficient amount of vocabulary and able to use them correctly. Thus, this research is purposed to figure out students’ vocabulary skill at SMK Grafika Bina Media and to figure out the problems faced by students in learning vocabulary. The research was done on Class X Design Graphic students which consists of 19 students. The methodology used in this research was descriptive method. In this research, the authors used interview and vocabulary mastery test which consists of 40 questions, 15 in multiple choice and 25 in essays to obtain the data. Based on the findings of this research, it can be stated that only 3 students managed to get >85 and most students get <70. Thus, it indicates that students’ skill in vocabulary is still low. Students also faced some difficulties in answering the questions because they don’t know the meaning of the words and some words are new for them.